Fabrication and photoelectrical characteristics of ZnO nanowire field-effect transistors - 付晓君 张海英 郭常新 徐静波 黎明 (Journal of semiconductors, 2009)
The fabrication and photoelectrical characteristics of suspended ZnO nanowire （NW） field-effect transistors （FETs） are presented. Single-crystal ZnO NWs are synthesized by a hydrothermal method. The fabricated FETs exhibit excellent performance. When Vds=2.5 V, the peak transconductance of the FETs is 0.396 μS, the average electron mobility is 50.17 cm2/（V·s）, the resistivity is 0.96 × 102 Ω·cm at Vgs = 0 V, and the current on/off ratio （Ion/Ioff） is approximately 105. ZnO NW-FET devices exposed to ultraviolet radiation （2.5 μW/cm2） exhibit punch-through and threshold voltage （Vth） shift （from-0.6 V to ＋0.7 V） and a decrease by almost half of the source-drain current （Ids, from 560 nA to 320 nA） due to drain-induced barrier lowering. Continued work is underway to reveal the intrinsic properties of suspended ZnO nanowires and to explore their device applications.